Application of Nursing Care for Patients With Chronic Obstructive Pulmonary Disease in Pulmonary Ward - Aini Yusra; Yulvi Hardoni; Zulharmaswita; Tintin Sumarni (CV. CENDIKIA JENIUS INDONESIA, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation that causes impaired ventilation and oxygenation. Patients with COPD frequently experience dyspnea, productive cough, sputum retention, fatigue, and decreased activity tolerance that require comprehensive nursing management. Appropriate nursing interventions are important to maintain airway patency, improve respiratory status, and prevent respiratory complications among hospitalized patients. Objective: This study aimed to describe the application of nursing care for patients with Chronic Obstructive Pulmonary Disease in the Pulmonary Ward of Mohammad Natsir Regional Hospital, Solok City. Results: The patient experienced shortness of breath, productive cough, difficulty expelling sputum, fatigue, and limited physical activity. Nursing diagnoses identified included ineffective airway clearance, ineffective breathing pattern, and activity intolerance. Nursing interventions implemented consisted of oxygen therapy, airway management, effective coughing exercises, chest physiotherapy, breathing exercises, semi-Fowler positioning, gradual mobilization, and energy conservation techniques. Evaluation findings demonstrated reduced dyspnea, improved respiratory rate, decreased sputum production, and better tolerance to physical activity after the interventions were implemented. Conclusion: The application of comprehensive nursing care contributed positively to respiratory improvement and patient comfort among COPD patients. Continuous respiratory monitoring, evidence-based nursing interventions, and individualized nursing care are important to optimize patient outcomes and prevent respiratory complications.